Law and legal systems: an introduction - Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan; Ahmad, Masum; Arowosaiye, Yusuf Ibrahim; Lilienthal, Gary (LexisNexis Malaysia Sdn Bhd, 2025)
[1-1] Law refers to the body of rules and principles governing the affairs of a community and is enforced through a set of establishments put in place which includes the police, the courts and prison systems. Law is established primarily to govern a society and to control the behaviour of its members, that is, to maintain the social order and protect persons and property from harm. A legal system refers to the framework of rules and institutions within a country that regulates the relationship between the government and its subjects and between the subjects themselves. The application of the legal system varies from country to country and is largely shaped by the unique history of a particular country. Generally, the most widespread legal systems in the world are the Civil Law, the Common Law and the Religious Law. Malaysia practices largely the Common Law System with limited application of the Islamic Legal System particularly on personal matters such as marriage, divorce, family relationships and property which are applicable only to Muslims and are enforced in the Syariah courts. Having said the above, in order to have a sound understanding of the business and commercial law in Malaysia, it is crucial at the outset to have a good grasp of the various aspects involving law and the legal systems. Hence, this chapter discusses the juristic and statutory definition of law, categories of law, the classifications of laws such as public law and private law, substantive law and procedure law, domestic law and international law, public international law and private international law among others. Further, the discussion will also feature the Islamic law enforced in Malaysia with reference to the Federal Constitution, the supreme law of the Federation as noted in article 4.